JOINT COUNCIL NO 64 OF CT - POWERS,J (Tufts Archival Research Center, 2007)
Letter from Connecticut Teamsters President Jack Powers to Ron Carey, President of the International Brotherhood of Teamsters. Expresses anger at boycott of Entenmann's Bakery coordinated Carey and Corporate Strategist Ron Carver. Indicates that boycott will harm union members and that Entenmann's, unlike Freihofer's and Philip Morris, has been Teamster-friendly.